(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2025)
In this work we propose to examine the utopian-dystopian discourse through a comparative study of two novels –Spanish American and Egyptian– of the beginning of 21st. That is to say; Burnt Palace (2007) by Edmundo Paz Soldán and Utopia (2008) by Ahmed Khaled Tawfiq. Our analysis will adopt a comparative perspective to explore how such socio-critical reflections have been treated from the perspective of both authors, and how they have become two paradoxes of Latin and Egyptian society. Likewise, we emphasize the narrative aesthetics of both study novels –according to Genette–, starting from protagonists, narrative view point, and Chronotopia. In our studies, we will follow a complete methodology, which includes the application of the comparative analytical method, and we give interest in the North American theory that depends on form and theme as fundamental elements in the narrative.